Diffusion Ignition Processes in MILD Combustion: A Mini-Review - Sorrentino, Giancarlo; Cavaliere, Antonio; Sabia, Pino; Ragucci, Raffaele; de Joannon, Mara (Frontiers in Mechanical Engineering, 2020)
MILD Combustion processes belong to new combustion technologies developed to achieve efficient and clean fuel conversion. The basic concept behind its implementation is the use of high levels of hot exhausted gas recirculation within the combustion chamber. They simultaneously dilute fresh reactants, to control system temperatures and pollutants emission, while promoting fuel complete oxidation. The combination of low maximum system working temperatures and high diluted mixtures with intense pre-heating delineate an oxidation process with unique chemical and physical features, such as uniformity of scalars at macroscale related to distributed reacting regions at microscale, extremely different from conventional flames. In turn, this requires the definition and characterization of new elementary processes, not ascribable to traditional deflagrative or diffusive flame structures, that in literature have been identified as “Diffusion Ignition”. The present Mini-Review reports on several literature characterization of such reactive structures under steady and unsteady conditions combining evidences from numerical, experimental and/or theoretical studies. Both premixed and non-premixed configurations were analyzed in terms of system temperature, heat release and species distributions as key parameters to describe the intrinsic nature of such new elementary processes. Analyses were realized changing the main system external parameters (mixture pre-heating temperature, dilution level in several feedings configurations) moving from traditional to MILD conditions. Results highlighted the “distributed ignition” nature of Ignidiffusive structures, with implication on the thickness of the oxidation structures in the mixture fraction space, the presence/absence of a pyrolysis region and the correlation of the maximum heat release with the mixture stoichiometric.